2014
DOI: 10.1016/j.jval.2014.08.692
|View full text |Cite
|
Sign up to set email alerts
|

Health Economic Evaluation of Canagliflozin in the Treatment of Type 2 Diabetes Mellitus in France

Abstract: Objectives: Two SGLT-2 inhibitors, CANA and DAPA, are recommended in the UK for combination therapy in T2DM. Through an insulin-independent mechanism of action, SGLT-2 inhibitors improve glucose levels, blood pressure, and weight with a low inherent risk of hypoglycaemia. The cost-effectiveness of using CANA or DAPA in combination with MET was evaluated in patients inadequately controlled with MET monotherapy, from the perspective of the UK NHS. MethOds: The ECHO-T2DM model was used to estimate 40-year outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This was also the case for canagliflozin 100 mg, based on economic evaluations in Spain56 and Poland,57 whereas canagliflozin 300 mg produced an ICER of €181356 and 45,008 zł57 compared with sitagliptin, respectively. Results from additional country-specific analyses versus sitagliptin also suggest that canagliflozin is likely to be a cost-effective option adjunct to metformin, in Ireland,58 France,59 Belgium,60 Slovakia,61 and the Czech Republic 62. Moreover, a NICE HTA for canagliflozin concluded that, due to small differences in costs and QALYs between canagliflozin and DPP-4 inhibitors, both canagliflozin 100 and 300 mg were recommended treatment options in patients inadequately controlled with metformin alone 63…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also the case for canagliflozin 100 mg, based on economic evaluations in Spain56 and Poland,57 whereas canagliflozin 300 mg produced an ICER of €181356 and 45,008 zł57 compared with sitagliptin, respectively. Results from additional country-specific analyses versus sitagliptin also suggest that canagliflozin is likely to be a cost-effective option adjunct to metformin, in Ireland,58 France,59 Belgium,60 Slovakia,61 and the Czech Republic 62. Moreover, a NICE HTA for canagliflozin concluded that, due to small differences in costs and QALYs between canagliflozin and DPP-4 inhibitors, both canagliflozin 100 and 300 mg were recommended treatment options in patients inadequately controlled with metformin alone 63…”
Section: Methodsmentioning
confidence: 99%
“…In particular, from the Canadian health care perspective, canagliflozin 100 and 300 mg provided QALY gains of 0.28 and 0.31, and cost savings of C$2560 and C$2217, respectively, over a time horizon of 40 years. 68 Canagliflozin also dominated sitagliptin across different countries, including Belgium, 60 France, 59 Norway, 54 and Portugal, 55 when both dosing schemes were assessed as a single intervention. Of note, additional economic evaluations concluded that canagliflozin was a cost-effective therapeutic option as add-on to metformin and sulfonylurea in Brazil, 69 Ireland, 58 Slovakia, 61 and the Czech Republic, 62 although it was associated with higher treatment costs compared with sitagliptin.…”
Section: Methodsmentioning
confidence: 99%